Pengaruh Muslim Spiritual Attachment terhadap Konflik Perkawinan pada Istri di Kota Makassar - Nur Fadillah; Asniar Khumas; Sitti Murdiana (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to examine the effect of Muslim spiritual attachment on marital conflict. This research was conducted with quantitative methods through the distribution of the scale with the number of research respondents as many as 125 wives in the city of Makassar. The data collection technique was done by purposive sampling technique. Data were analyzed using logistic regression analysis technique with the help of JASP version 0.14.1.0. The results showed that among the three dimensions of Muslim spiritual attachment, only the secure relationship dimension had a significant effect on marital conflict with a B value of (-0.602). The dimensions of separation protest and the positive dimensions of the model of self have no significant effect on marital conflict. The value of R2 = 0,059 which means that the three dimensions of Muslim spiritual attachment, namely the dimensions of secure relationship, separation protest, and positive model of self together are able to explain the marital conflict variable with conformity of 5.9%.